Pretreatment of Mesenchymal Stem Cells Manipulates Their Vasculoprotective Potential While Not Altering Their Homing Within the Injured Gut. (29th June 2015) - Kavanagh, Dean P.J.; Suresh, Shankar; Newsome, Philip N.; Frampton, Jon; Kalia, Neena
Abstract: Mesenchymal stem cells (MSCs) have shown therapeutic promise in many experimental and clinical models of inflammation. However, a commonly reported feature of MSC transplantation is poor homing to injured tissues. Previously, we have shown that pretreatment with cytokines/chemical factors enhances hematopoietic SC adhesion within intestinal microvasculature following ischemia-reperfusion (IR) injury. Using intravital microscopy, the ability of similar pretreatment strategies to enhance the recruitment of murine MSCs to murine intestinal microvasculature following IR injury was investigated. Primary MSCs were isolated from bone marrow and selected on the basis of platelet-derived growth factor receptor-α and SC antigen-1 positivity (PDGFRα + /Sca-1 + ). MSC recruitment was similar in IR injured gut mucosa when compared with sham operated controls, with limited cell adhesion observed. MSCs appeared contorted in microvessels, suggesting physical entrapment. Although not recruited specifically by injury, MSC administration significantly reduced neutrophil recruitment and improved tissue perfusion in the severely injured jejunum. Vasculoprotective effects were not demonstrated in the lesser injured ileum. Pretreatment of MSCs with tumor necrosis factor (TNF)-α, CXCL12, interferon (IFN)-γ, or hydrogen peroxide did not enhance their intestinal recruitment. In fact, TNFα and IFNγ removed the previous therapeutic ability of transplanted MSCs to reduce neutrophil infiltration and improve perfusion in the jejunum. We provide direct evidence that MSCs can rapidly limit leukocyte recruitment and improve tissue perfusion following intestinal IR injury. However, this study also highlights complexities associated with strategies to improve MSC therapeutic efficacy. Future studies using cytokine/chemical pretreatments to enhance MSC recruitment/function require careful consideration and validation to ensure therapeutic function is not impeded. Stem Cells   2015;33:2785–2797